2007
DOI: 10.1021/ma070731k
|View full text |Cite
|
Sign up to set email alerts
|

Structure Model of a Poly(vinyl alcohol) Film Uniaxially Stretched in Water and the Role of Crystallites on the Stress−Strain Relationship

Abstract: We propose a structure model of a poly(vinyl alcohol) (PVA) film during uniaxial stretching in water. In addition to the relaxation of microfibrils and the extension of interfibrillar amorphous regions shown in our previous paper, it was described that the strain-induced crystallization takes place in the interfibrillar extended amorphous regions, which bear the increasing stress with strain, by conducting simultaneously the tensile stress−strain measurement with the wide-angle X-ray diffraction (WAXD) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 34 publications
5
55
0
Order By: Relevance
“…The XRD patterns obtained before stretching and at the end of holding at each temperature (70 C, 120 C, 160 C and 170 C) reveal that the Herman's orientation factor [22,41] in crystalline region increases as the temperature increases (Fig. 7).…”
Section: Mechano-optical Behavior In Stretching and Holding Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD patterns obtained before stretching and at the end of holding at each temperature (70 C, 120 C, 160 C and 170 C) reveal that the Herman's orientation factor [22,41] in crystalline region increases as the temperature increases (Fig. 7).…”
Section: Mechano-optical Behavior In Stretching and Holding Processmentioning
confidence: 99%
“…This study was conducted using an off-line characterization technique at different stages. To follow the structure evolution real time, Miyazaki [21,22] used a stretching instrument that could perform stressestrain experiments coupled with small angle X-ray scattering (SAXS) or wide angle X-ray diffraction (WAXD) simultaneously to characterize the structural development of PVA film during uniaxial stretching in water. By means of WAXD and SAXS, the structural development of crystalline regions in swollen state were characterized, leading to observation of strain induced crystallization in the extended amorphous regions with increasing the strain.…”
Section: Introductionsmentioning
confidence: 99%
“…Accompanying with the microfibrillation, the amorphous chains between the microfibrils highly orient in the film stretching direction and so‐called strain‐induced crystallization occurs in part of the highly oriented amorphous regions, as indicated with the increase in the crystallinity index above the strain of about 170% in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the 2‐D WAXD patterns obtained on stretching were integrated within 90° from vertical direction for obtaining the 1‐D radial diffraction profiles. Furthermore, as described in our early articles , 1‐D diffraction profiles were decomposed into two crystalline peaks ( true(101true)true(101¯true) doublet and true(200true) planes; the b‐axis is defined to be parallel to the chain direction) and one amorphous halo in the examined region, q = 10 − 18 nm −1 for the estimation of crystallinity. The peak type was chosen to be Gaussian.…”
Section: Discussionmentioning
confidence: 99%
“…But the PVA fibers used in these studies were mostly obtained by solution process. Miyazaki 10 proposed a structure model of PVA film stretched uniaxially in water. The result showed that the strain induced crystallization took place in the interfibrillar extended amorphous regions, which produced the increasing stress with increasing strain, and the lamellar stacked in the film contribute to the system hardening, which was attributed to the extension of the interfibrillar amorphous regions.…”
Section: Introductionmentioning
confidence: 99%